(untitled) (Latakia University Journal -Basic Sciences Series, 2023)
Recently, global interest in medicinal plants used in folk medicine has increased as an important source of natural molecules with different biological activities and their role in discovering and developing new drugs. Among the medicinal plants used in folk medicine in Syria is Centaurium pulchellum, known locally as " AL-Marar ". The aerial parts of the plant were collected from a mountainous area in Latakia Province, Syria. The essential oil was obtained by the Clevenger-type apparatus with a yield of 0.88%. Seventy-five compounds, representing 99.56% of the total oil, were identified by GC-MS technique. The major identified compounds were: β-Damascenone (13.18%), Ledol (10.73%), Hexahydrofarnesyl acetone (8.42%), (E)-Verbenol (6.37%). In this study, GC-MS analysis revealed for the first time the dominance of terpene compounds on the essential oil content of the aerial parts of the AL-Marar plant, which have a variety of biological activities. It emphasizes how significant this plant is as a potential plant drug for use in food and medicine applications and encourages more study of this plant to create novel plant-based pharmaceutical formulations.